2014
DOI: 10.1186/1745-6215-15-473
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Paramedicine in the Community (EPIC): study protocol for a randomized controlled trial

Abstract: BackgroundThe incidence of chronic diseases, including diabetes mellitus (DM), heart failure (HF) and chronic obstructive pulmonary disease (COPD) is on the rise. The existing health care system must evolve to meet the growing needs of patients with these chronic diseases and reduce the strain on both acute care and hospital-based health care resources. Paramedics are an allied health care resource consisting of highly-trained practitioners who are comfortable working independently and in collaboration with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…A full description of the EPIC model and study methods has been previously published elsewhere (Drennan et al. ). The primary study (a randomized control trial) was conducted in partnership with two paramedic services and four family health care teams and funded through a special funding allocation from the Ontario Ministry of Health and Long‐Term Care.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the EPIC model and study methods has been previously published elsewhere (Drennan et al. ). The primary study (a randomized control trial) was conducted in partnership with two paramedic services and four family health care teams and funded through a special funding allocation from the Ontario Ministry of Health and Long‐Term Care.…”
Section: Methodsmentioning
confidence: 99%
“…From a paramedic perspective, there is an opportunity to both be a resource for the patient and provide better utilisation of other available resources through the assessment, influence and improvement of the patient's SOC. Paramedics are often the first, and sometimes the only, point-of-care for many people experiencing unscheduled health events (37). In addition to managing emergencies, paramedics are trained to recognise the signs and symptoms of conditions and take appropriate action before the situation becomes an emergency.…”
Section: The Potential Role Of Paramedics In Building Health Resiliencementioning
confidence: 99%
“…Program initiated enrolment followed a case management approach designed for frequent paramedic service callers or patients deemed eligible for enrolment through other disease management programs. In total, eight community paramedicine programs described this type of enrolment; in four programs this was the only means of enrolment (31,33,34,36,37,41,45,47). Most programs included more than one means of enrolment (see Table 2).…”
Section: Aspects Of Care Planningmentioning
confidence: 99%
“…Four programs employed a model of care similar to the ECP model (26,37,41,45) where care was available at a patient's time of need with a focus on care provision "in-place." These programs, along with two other programs (32,34) were classified as having patient initiated enrolment. Three of the four programs that identified themselves as ECP models also indicated that the service could initiate contact with identified individuals (37,41,45) while the fourth indicated that the service also actively recruited participants (26).…”
Section: Aspects Of Care Planningmentioning
confidence: 99%